Analisis Mekanisme Penetapan Harga Jual Dalam Perspektif Prinsip-Prinsip Ekonomi Syariah (Di Toko Berkah Jl. Depati Parbo Jambi) - Suci Putri Utami; Titin Agustin Nengsih; Muthmainnah Muthmainnah (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2023)
Price fixing is a price fixation that has been determined by the party entitled to determine the price. In setting the price, an item must be agreed upon and generally applicable. However, there are still buying and selling that contain elements of injustice between one buyer and another. There are several things that motivate the author to conduct research on the selling price setting process at the Berkah shop because it is classified as unique, to find out whether the price setting at the Berkah shop is in accordance with the perspective of the Sharia Economy. The results of the study show that the Islamic economic review in pricing at the Berkah Shop is in accordance with Islamic law, the price set is still relatively fair. With this price setting, it can meet the needs of the community, meet the needs of households, and meet the needs of the community, especially those on Jl. Depati Parbo Jambi city in the long term. Pricing at Toko Berkah can also create a sense of mutual assistance, because pricing at Toko Berkah includes an element of mutual help.